1979
DOI: 10.1042/bj1780397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collagen, ionophore A23187 and prostaglandin E1 on the phosphorylation of specific proteins in blood platelets

Abstract: Human platelets that had been preincubated with 5-hydroxy[(3)H]tryptamine and [(32)P]P(i) were stirred with various agents; the secretion of 5-hydroxy[(3)H]tryptamine from platelet granules and the radioactivity of platelet [(32)P]phosphopolypeptides separated by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis were then measured. Exposure of the platelets to collagen fibres or ionophore A23187 selectively increased the phosphorylation of polypeptides with apparent mol.wts. of 47000 (P47) and 20000 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(72 citation statements)
references
References 34 publications
4
66
1
1
Order By: Relevance
“…1 Its 350 amino acid sequence can be divided into 3 motifs: PH domains at the aminoand carboxy-termini of the molecule and an intervening DEP domain. [2][3][4] A short stretch of amino acids between the aminoterminal PH domain and the DEP domain contains 3 sites of phosphorylation (Ser113, Thr114, and Ser117) by PKC, which are essential for the function of pleckstrin-1.…”
Section: Introductionmentioning
confidence: 99%
“…1 Its 350 amino acid sequence can be divided into 3 motifs: PH domains at the aminoand carboxy-termini of the molecule and an intervening DEP domain. [2][3][4] A short stretch of amino acids between the aminoterminal PH domain and the DEP domain contains 3 sites of phosphorylation (Ser113, Thr114, and Ser117) by PKC, which are essential for the function of pleckstrin-1.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation, by many external stimuli, is associated with phosphorylation and dephosphorylation reactions (Lyons et al, 1975;Haslam & Lynham, 1977;Haslam et al, 1979;Daniel et al, 1981;Imaoka et al, 1983;Schafer et al, 1986;Touqui et al, 1986). This has led us to study the possibility that the dephosphorylating enzyme alkaline phosphatase, by removing phosphate groups from the external platelet membrane, might modulate the platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that thrombin treatment of intact 32PO43-_loaded human platelets resulted in phosphorylation of two specific peptides of M, 41,000 and 20,000 (termed P7P and P9P, respectively) as assessed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE)' (8). The time-course of phosphorylation was similar to that of serotonin secretion (release I [9]); this suggests that phosphorylation of these two peptides may be important in induction of the release reaction.…”
Section: Introductionmentioning
confidence: 99%